Looking Back to the Potlatch as a Guide to Truth, Reconciliation, and Transformative Learning. (5th March 2019) - Wilson, Justin; Nelson‐Moody, Aaron
Abstract: This chapter describes the potlatch as a methodology to engage culturally diverse classrooms in liberation curriculum. The Potlach is a high‐context, community‐based, participatory method offering three intra/interpersonal reflexive waypoints teachers can use when designing and delivering transformative learning.